Isolation, Identification, and Evaluation of Antimicrobial Activity of Active Compound Produced by Marine Actinomycetes isolate A32 - Sunaryanto, Rofiq; Marwanta, Edy (Annales Bogorienses, 2015)
The continuation of new antibiotics exploration becomes an important research program in the world for pharmaceutical and agricultural applications. Marine filamentous bacteria such as actinomycetes have been widely used as an important biological tool to generate a variety of new secondary metabolites, such as antibiotic. The aim of this study was to obtain identified active compound and determine its antimicrobial activity. Isolation, identification, and antimicrobial activity assay of active compound produced by marine actinomycetes isolate A32 had been conducted. Production of active compound using isolate actinomycetes A32 was conducted involving glucose, yeast, peptone medium. The fermentation was carried out at 30 ºC for 5 days. The broth of supernatant was extracted using ethyl acetate. Purification of active compound used chromatography column and eluted stepwise with the chloroform and methanol solvents. Antimicrobial activity was monitored using agar disc diffusion, and microbial test was conducted by analyzing the samples diameter of clear zone towards Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Bacillus subtilis ATCC 66923, and Candida albican BIOMCC 00122. Results of isolation and purification of active compound produced by actinomycetes isolate A32 show that this compound has a molecular weight of 503.1 g/mol with molecular formula C26H37N3O7. Furthermore, this compound was suspected as Madumycin II after analysis of spectrum using 1HNMR and COSY. The antimicrobial activity assay confirms that this active compound inhibited the growth of Staphylococcus aureus ATCC 25923 and Candida albican BIOMCC 00122.